OSTEOBLAST AND GINGIVAL FIBROBLAST MARKERS IN DENTAL IMPLANT STUDIES - Pivodova, Veronika; Frankova, Jana; Ulrichova, Jitka (Biomedical papers, 2011)
Background: Dental implants are a suitable option for the replacement of some or all missing teeth. Their main function is to secure the stability of the artificial tooth. The implant material interacts with several cell types including osteoblasts, gingival fibroblasts, periodontal ligament fibroblasts and monocytes. The most common material used is pure titanium which is corrosion resistant and has an elasticity modulus similar to that of bone. In recent years, diverse modified titanium surfaces have also been developed. The wound healing around the implant is a complex process that determines how well the host can heal and accept the implanted material. For this reason, search for markers of the biocompatibility of these new materials is paramount. To identify markers found to be suitable for studying the biocompatibility of dental implants.Methods: Review of Pubmed and Web of Science databases for the years 1958-2010.Conclusions: The surface of dental implant material should enhance firm attachment of the implant to junctional epithelium, soft connective tissue and bone. For the purposes of dental implant biocompatibility studies, a number of markers produced by osteoblasts or by cells of periodontal ligament have been proposed. In general, the most typical markers for osteoblasts and fibroblasts are alkaline phosphatase and collagen I, respectively. The involvement of both cell types in the inflammatory response is primarily evaluated by determination of tumour necrosis factor α and proinflammatory interleukins.
Keywords: Osteoblasts/Gingival fibroblasts/Extracellular matrix proteins/Dental implants